Burnout, work disruptions, interpersonal and psychosomatic problems–degree-specific comparison of students at a German university - Gumz, A.; Brähler, E.; Heilmann, V. K.; Erices, Rainer (Gesundheitswesen, 2014)
In the context of the public debate on psychological strain among students, the prevalence of burnout, procrastination, test anxiety, other work disruptions, interpersonal problems and psychic symptoms were analyzed depending on academic degree. The data of 358 college students (of Leipzig University) were examined. The academic degree had only a marginal effect on burnout- and work disruptions-related variables. In terms of interpersonal problems and psychic symptoms, differences between students were identified, depending on the academic degree. Diploma students reported many complaints, whereas undergraduates aspiring for a State Examination, were comparatively less affected. Knowledge of the population-specific psychological load is useful in order to develop preventive and therapeutic measures.
EVALuna2:5659